Influence of Fluoride Ions in Artificial Saliva Solution to Corrosion Behavior of Ti-6Al-4V and Ti-10Mo-4Zr Titanium Alloys - Loch, Joanna; Krawiec, Halina (Journal of Casting & Materials Engineering, 2018)
Titanium alloys used in medical applications (especially dentistry) are exposed to the actions of various compounds that appear periodically in the mouth. Fluorine compounds are dangerous for the surface of titanium alloys, because they generate a dissolution of the passive layer. In this way, they destroy the surface of dental implants and cause the absorption of metal ions into the human body.The presented work was aimed to describe the effect of fluoride ions on the corrosive behavior of the commercial Ti-6Al-4V and new Ti-10Mo-4Zr alloys that can be used in stomatology. Electrochemical measurements such as open circuit potential (OCP), linear sweet voltamperometry (LSV) and impedance spectroscopy (EIS) were performed to get information on the corrosive behavior of titanium in artificial saliva solutions (MAS) with different concentrations of NaF. It has been revealed that a high concentration of fluoride ions enhance the current density in the anodic domain, especially for the Ti-10Mo-4Zr alloy. EIS measurements performed at a potential of 0.5 V vs. AgCl (3 M KCl) show that the Ti-10Mo-4Zr alloy has a typical two-layer structure of its passive film. This passive film consists of the outer and inner layers, respectively. The resistance of the outer layer is significantly lower than the resistance of the inner layer.